WHAT CHANGES IN PERFUSION AND MYOCARDIAL FUNCTION AFTER LATE REVASCULARIZATION OF ACUTE MYOCARDIAL INFARCTION? - E. N. Ostroumov; E. V. Migunova; E. D. Kotina; O. G. Sinyakova; G. A. Gazaryan; V. A. Ryabinin; N. E. Kudryashova (Неотложная медицинская помощь, 2017)
Aim. To determine the influence of the time gap between acute myocardial infarction with ST-segment elevation and intracoronary intervention performed later than 2.5 hours on myocardium, we studied indicators of perfusion over time with an aid of SPECT, including intraventricular asynchrony (2–4 days and 6–8 months after stent installation).Materials and method. We observed 22 patients with multivessel coronary lesion. The Russian program with the analysis of perfusion, function and the phase images was used in SPECT synchronized with ECG.Results. Showed that the time gap prior to coronary intervention in the acute phase of myocardial infarction may be directly connected with the increase in impaired perfusion during the end-systole and the severity of pathological intraventricular asynchrony without ECG signs. All patients had significantly decreased wall mobility and intraventricular asynchrony together with increased R-R interval in the late period (after 6–8 months) independently from the coronary intervention time. In patients of group 1 (coronary intervention within 6 hours), focal transmural lesions of myocardium significantly decreased.Conclusion. Late revascularization help decrease intraventricular asynchrony reducing the risk of heart failure in future.